Co-design Workshop on Inclusive Business Models for Aquaculture in Small Reservoirs in Northern Ghana - Appiah, Sarah; Zane, Giulia; Gbodji, Kekeli Kofi (International Water Management Institute, 2025)
On 10 June 2025, the International Water Management Institute (IWMI) organized a Co-Design Workshop in Tamale, Ghana. The workshop, held under the CGIAR Sustainable Animal and Aquatic Foods (SAAF) Science Program, aimed to co-develop inclusive business models for aquaculture in small reservoirs in northern Ghana. The event brought together 37 participants from across the aquaculture ecosystem, including farmers, private sector actors, policymakers, and researchers. The workshop sought to identify key barriers, explore scaling opportunities, and co-develop inclusive business models for small-scale aquaculture in the many small reservoirs available across the 5 regions of northern Ghana. Participants built on lessons from IWMI’s pilot interventions in four communities in the North-East Region, which demonstrated the feasibility of reservoir-based aquaculture. Discussions highlighted persistent challenges such as limited access to finance, high input costs, limited access to extension services, and weak market linkages. Farmers expressed a preference for catfish over tilapia due to its resilience and market demand. Through group work, participants proposed several inclusive business models, including integrated farming, polyculture, cooperative and contract farming, public–private partnerships, and empowerment models emphasizing capacity building and networking across the value chain. They recommended piloting multiple models, ensuring strong community engagement, selecting committed participants, and starting small to refine approaches before scaling. In the next phase, IWMI will conduct household surveys across several communities to assess local preferences regarding fish types, processing, and benefit-sharing mechanisms to inform the refinement and testing of scalable, inclusive, and context-appropriate business models.